Institutional Structuring of Fisheries Extension and Its Impact on Personnel Administration in the Ministry of Marine Affairs and Fisheries - Prianggoro, Bimo Adi; Halim, Halim; Syukur, Alam Tauhid (Universitas Muhammadiyah Sidoarjo, 2022)
The enactment of Law Number 11 of 2019 and Presidential Regulation Number 78 of 2021 has a significant impact on the existence of main office for fisheries extension officers (Satminkal). As a result, 4 research organization which have an Satminkal function must be integrated with National Research and Innovation Agency (NRIA/BRIN). Related to this, the research aims to examine and analyze the model of institutional arrangement of fisheries extension officers and its impact on personnel administration within the Ministry of Maritime Affairs and Fisheries (MMAF). Based on qualitative descriptive methods and analysis covering theoretical, sociological, and juridical aspects, with the increasingly complex dynamics of fisheries extension and the disappearance of extension services from the research organization of Satminkal, MMAF has the resources and authority to strengthen the institutional status of fisheries extension, so as to minimize the impact of personnnel administration. for fisheries extension officers. It is recommended to MMAF for re-design and strengthen the fisheries extension institution by establishing Fisheries Extension Stations in 34 provinces taking into account of geographical environment, potential assets of MMAF